International Conference on Oriental Thinking and Fuzzy Logic Celebration of the 50th Anniversary in the era of Complex Systems and Big Data - Cao, Bing-Yuan.; Wang, Pei-Zhuang.; Liu, Zeng-Liang.; Zhong, Yu-Bin.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This proceedings book presents edited results of the eighth International Conference on Fuzzy Information and Engineering (ICFIE'2015) and on Oriental Thinking and Fuzzy Logic, in August 17-20, 2015, in Dalian, China. The book contains 65 high-quality papers and is divided into six main parts: "Fuzzy Information Processing", "Fuzzy Engineering", "Internet and Big Data Applications", "Factor Space and Factorial Neural Networks", "Information Granulation and Granular Computing" as well as "Extenics and Innovation Methods".
I Fuzzy Information Processing -- II Fuzzy Engineering -- III. Internet and Big Data Applications -- IV. Factor Space and Factorial Neural Networks -- V. Information Granulation and Granular Computing -- VI. Extenics and Innovation Methods -- VII. Others.
Keywords: Computational intelligence; Artificial intelligence; Dynamics; Nonlinear theories; Computational Intelligence; Artificial Intelligence; Applied Dynamical Systems